Association of Infantile Osteopetrosis and Rickets: A Case Report - Yasemin Sancak; Deniz Çakır; F. Deniz Aygün; Erdal Eren; Ömer Faruk Tarım; Solmaz Çelebi (Güncel Pediatri)
Introduction: Osteopetrosis is a rare disorder of osteoclast function resulting in failure of resorption and increased bone density. Rickets is a paradoxical complication of osteopetrosis. In this article, we report a 3-month old infant, examined because of right inguinal swelling and hepatosplenomegaly who was diagnosed with osteopetrosis and rickets, a rare association. Case: A 3-month old infant was referred to Pediatric Infectious Disease department to rule out congenital CMV infection because of positivity of CMV IgM and CMV Ig G detected during examination for right inguinal swelling and hepatosplenomegaly. Antenatal history of the baby was normal. On physical examination, he did not have head control and eye contact, he had bilateral horizontal nystagmus, a 5-cm hepatomegaly, a 6-cm splenomegaly, and right inguinal hernia. The laboratory evaluation revealed serum Ca of 9.3 mg/dl (8.4-10.2), P of 2.2 mg/dl (2.3-4.7), and ALP of 1139 U/L (40-150). Hyperdense appearence was seen in chest x-ray, and whole radiological skeletal survey revealed diffusely increased bone density, ‘space alien’ sign in craniography, sandwich sign in vertebrae, and enlargement of costocondral junction on chest radiogram. With laboratory and radiologic findings, the patient was diagnosed as osteopetrosis associated with rickets.Conclusion: Association of osteopetrosis and ricets is rare and paradoxical. Early diagnosis and treatment improves patients’ life expectancy. Therefore detection and traetment of rickets before bone marrow transplantation increases success of treatment.(Journal of Current Pediatrics 2012; 10: 40-3)